PRICE AND ISLAMIC SERVICE QUALITY AS DETERMINANTS OF SMES SATISFACTION IN ISLAMIC MICROFINANCE: EVIDENCE FROM KUDUS, INDONESIA - Krisnanda, Krisnanda; Ratnawati, Dwi Puji; Hendriyanto N., Dennyca; Tamrin, Muhammad Husni (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
Small and Medium Enterprises (SMEs) are a key driver of Indonesia’s economy, yet they often face limited access to formal financing. Islamic microfinance institutions (IMFIs) provide Shariah-compliant financial solutions that address this gap. This study examines the influence of price and Islamic service quality on SMEs’ satisfaction with Islamic microfinance in Kudus, Indonesia. Using a quantitative approach, data were collected from 100 SME respondents through structured questionnaires and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that both price (t = 3.434, p < 0.05, f² = 0.131) and Islamic service quality (t = 5.490, p < 0.001, f² = 0.297) have a positive and significant effect on SMEs’ satisfaction, with the model explaining 47.3% of the variance (R² = 0.473). These findings highlight that competitive pricing and high quality Shariah compliant services are essential in enhancing SMEs’ satisfaction. The study provides practical insights for Islamic microfinance institutions to improve service delivery and strategic pricing, while contributing to the literature on customer satisfaction in Islamic finance.